Eye color as an indicator of social rank in the fish Nile tilapia - Volpato, Gilson Luiz [UNESP]; Luchiari, A.C. [UNESP]; Duarte, C.R.A. [UNESP]; Barreto, R.E. [UNESP]; Ramanzini, G.C. [UNESP] (Associação Brasileira de Divulgação Científica (ABRADIC), 2003)
We investigated the association of eye color with the dominant-subordinate relationship in the fish Nile tilapia, Oreochromis niloticus. Eye color pattern was also examined in relation to the intensity of attacks. We paired 20 size-matched fish (intruder: 73.69 ± 11.49 g; resident: 75.42 ± 8.83 g) and evaluated eye color and fights. These fish were isolated in individual aquaria for 10 days and then their eye color was measured 5 min before pairing (basal values). Twenty minutes after pairing, eye color and fights were quantified for 10 min. Clear establishment of social hierarchy was observed in 7 of 10 pairs of fish. Number of attacks ranged from 1 to 168 among pairs. The quartile was calculated for these data and the pairs were then divided into two classes: low-attack (1 to 111 attacks - 2 lower quartiles) or high-attack (112 to 168 attacks - 2 higher quartiles). Dominance decreased the eye-darkening patterns of the fish after pairing, while subordinance increased darkening compared to dominance. Subordinate fish in low-attack confrontations presented a darker eye compared to dominant fish and to the basal condition. We also observed a paler eye pattern in dominants that shared low-attack interactions after pairing compared to the subordinates and within the group. However, we found no differences in the darkening pattern between dominants and subordinates from the high-attack groups. We conclude that eye color is associated with social rank in this species. Moreover, the association between eye color and social rank in the low-attack pairs may function to reduce aggression.
Keywords: Aggression; Eye color; Social hierarchy; Social stress; Fish; Oreochromis niloticus